Synergies between the Escazú Agreement and the 2030 Agenda on Sustainable Development for Latin America and the Caribbean (Sustainability in Debate, 2023)
This article aims to determine the main synergies between the Escazú Agreement and the 2030 Agenda on sustainable development, which can be exploited for the comprehensive and effective fulfilment of the SDGs. The qualitative approach and the deductive method were applied, considering the principles of environmental democracy and sustainable development as a framework for analysis. The United Nations LinkedSDG application was also used, which performs a semantic correlation analysis between public policy documents and the SDGs. The results show that the pillars of the Escazú Agreement are enablers and accelerators of the 2030 Agenda by creating the conditions for its mainstreaming in decision-making, implementation at the local level and support for actions designed to achieve the SDGs. It is concluded that implementing the Escazú Agreement in coordination with the strategies for fulfilling the SDGs in Latin America is an opportunity for the social legitimisation of public policies.